Cardiovascular Risk Factors In Hypertension In Middle-Aged Patients - Jalilova Umida Dzhumayevna (American Journal of Biology and Natural Sciences, 2024)
Hypertension (HTN) is one of the most common cardiovascular diseases. The importance of hypertension is determined by its negative impact on health status, long-term prognosis, quality and length of life [1]. Long-term hypertension causes damage to the body’s major organs and systems, such as the vascular system, heart, kidneys, and brain. The presence of hypertension is a proven factor in the development of a number of serious diseases associated with increased disability and death, such as ischemic and hemorrhagic stroke, transient ischemic attacks, myocardial infarction, heart failure and chronic kidney disease.